Flavius Areobindus – the one-war general - Leszka, Mirosław (Balcanica Posnaniensia. Acta et studia, 2020)
The article is dedicated to Flavius Areobindus, a member of military aristocracy during the turn of the 5th and the 6th centuries; who was a magister militum per Orientem and a consul in the year 506. Areobindus appears more explicitly in the sources only in relation to the Byzantine-Persian war of 503–505. He is also referenced in the context of religious developments in Constantinople that took place in November, 512. At that point, with no contribution of his own, he was named a candidate to the imperial throne by the rebels against the emperor Anastasius. He was a husband of Anicia Juliana, one of the most prominent women of the early Byzantium.